Understanding the challenges of personality disorders. - Barnes I (Canadian Nursing Home)
Residents with Alzheimer's dementia are recognized by their short-term memory loss and the fact that they are only able to 'live in the moment.' In contrast, residents with a personality disorder are recognized by their emotionalism - or lack of their controlling and manipulating behaviours, and their overall poor coping strategies. Facility staff initially welcome the new resident who is able to speak clearly and carry on a conversation. But, as staff will discover, this resident can create chaos, crises and drama in the facility.